How William Shatner changed the world [videorecording (DVD)] - Jones, Julian; Jones, Julian; Walter, Chip; Shatner, William (Allumination FilmWorks, 2007)
Can a TV show really change the way we interact with our world? From communicator-style flip phones to virtual reality and more, see how much the show Star Trek has influenced our everyday life.